Composite coating preparation method and composite coating
By preparing composite coatings on the surface of titanium alloy components, using microarc oxidation, pore sealing and vapor deposition technologies, the problems of insufficient wear resistance, galvanic corrosion resistance and thermal salt corrosion resistance during service were solved, and significant improvements in wear resistance and corrosion resistance were achieved.
Patent Information
- Application Number
- CN202411770160.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-04
AI Technical Summary
During service, titanium alloy components have problems such as insufficient wear resistance, galvanic corrosion resistance and thermal salt corrosion resistance, resulting in a decrease in reliability and service life.
The preparation method of composite coating is adopted, including the activation-treated MoS2 nanopowder uniformly dispersing in the electrolyte solution, microarc oxidation treatment is carried out to form a TiO2/MoS2 layer, followed by multi-step sealing treatment in the sealing solution, and finally, the Ti/MoS2 layer is formed by vapor deposition method to form a composite coating that is resistant to wear.
It significantly improves the friction-reduction and wear resistance and corrosion resistance of titanium alloy, extends the service life of titanium alloy components, and improves its reliability in complex working conditions.
Smart Images

Figure CN119243287B_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present disclosure relate to the technical field of metal coatings, and in particular, to a preparation method of a composite coating and the composite coating. Background Art
[0002] Titanium alloys, with their advantages of lightweight, high strength, and high-temperature resistance, are ideal materials for the development of major industrial equipment towards larger sizes, complex service environments, harsher component operating conditions, and longer service life requirements. They are widely used in aerospace, marine, nuclear energy, chemical, and medical fields. However, in actual applications, titanium alloy components suffer from insufficient wear resistance, galvanic corrosion resistance, and hot salt corrosion resistance during service. This can easily lead to a decrease in the reliability and service life of these titanium alloy components during use, and even affect the operational safety of the entire equipment.
[0003] To solve this problem, surface strengthening can be used to improve the surface performance of titanium alloy components. Currently, the research and development of titanium alloy surface coating materials mainly focuses on improving wear resistance; however, on the basis of wear resistance, how to reduce galvanic corrosion between titanium alloys and dissimilar materials and hot salt corrosion in high-temperature salt environments has also become an urgent problem to be solved. Summary of the Invention
[0004] The purpose of the present disclosure is to provide a method for preparing a composite coating and a composite coating, thereby overcoming, at least to a certain extent, the problem of how to reduce galvanic corrosion between titanium alloys and dissimilar materials and hot salt corrosion in high-temperature saline environments due to the limitations and defects of related technologies.
[0005] According to one aspect of the present disclosure, there is provided a method for preparing a composite coating, comprising:
[0006] Step 1: Evenly dispersing the activated MoS2 nanopowder in the electrolyte to obtain a composite electrolyte;
[0007] Step 2: placing the titanium alloy substrate in the composite electrolyte for micro-arc oxidation treatment to form a micro-arc oxidation layer with TiO2 / MoS2 on the surface of the titanium alloy substrate;
[0008] Step 3: Immersing the titanium alloy substrate with the TiO2 / MoS2 micro-arc oxidation layer in a sealing solution, followed by drying to obtain a substrate with a sealed TiO2 corrosion-resistant layer;
[0009] Step 4: Place the substrate with the sealed TiO2 corrosion-resistant layer in the vacuum chamber of the vapor deposition equipment as the anode, use the MoS2 target and the Ti target as the cathode, and perform coating treatment in an argon atmosphere with a vacuum degree of 1 Pa to form a wear-resistant composite coating on the surface of the substrate with the sealed TiO2 corrosion-resistant layer.
[0010] In an exemplary embodiment of the present disclosure, the activated MoS2 nanopowder used in the preparation process of the composite electrolyte is obtained by the following method: 10-20g of MoS2 nanopowder is immersed in a mixture of 0.05-0.1g of sodium dodecyl sulfate and 200-300g of ethanol and stirred for 2h for activation treatment to obtain an activated mixed solution, and the activated mixed solution is dried and sieved to obtain activated MoS2 nanopowder.
[0011] In an exemplary embodiment of the present disclosure, the preparation process of the composite electrolyte is obtained as follows: 1-5g / L activated MoS2 nanopowder, 10-15g / L sodium silicate, 0.5-1g / L sodium hypophosphite, 2-5g / L sodium tungstate, and 2-8ml / L glycerol are prepared into an electrolyte, continuously stirred for 1-2h, and ultrasonically vibrated for 0.5-1.5h to evenly distribute the activated MoS2 nanopowder in the electrolyte.
[0012] In an exemplary embodiment of the present disclosure, in the preparation process of the micro-arc oxidation layer with TiO2 / MoS2, the frequency used in the micro-arc oxidation treatment process is 400-800 Hz, the positive duty cycle is 5-30%, the negative duty cycle is 5%-30%, the forward voltage is 350-500 V, the negative voltage is 10-50 V, and the oxidation time is 20-40 min.
[0013] In an exemplary embodiment of the present disclosure, the sealing liquid is prepared by the following method:
[0014] 1) Mixing 0.5-1.5 g / L of a silane coupling agent with 2-10 g / L of an organic solvent to obtain a solvent mixing result;
[0015] 2) Stirring the solvent mixture for 36-48 hours to activate the solvent mixture and obtain a solvent activation result;
[0016] 3) Adding 5-10 g / L potassium fluorozirconate, 1-3 g / L nano titanium dioxide, and 1-5 g / L triethanolamine to the solvent activation result and ultrasonically shaking for 0.5 h to obtain the sealing solution.
[0017] In an exemplary embodiment of the present disclosure, the substrate with a sealed TiO2 corrosion-resistant layer is prepared as follows: a titanium alloy substrate with a TiO2 / MoS2 micro-arc oxidation layer is placed in a sealing liquid and soaked for 5-10 minutes, and the soaked titanium alloy substrate is placed in an oven and baked at 160°C for 15 minutes, and then the baking is repeated 3-5 times and then dried again for 30 minutes to obtain a substrate with a sealed TiO2 corrosion-resistant layer.
[0018] In an exemplary embodiment of the present disclosure, the composite coating is prepared by: 1) placing a substrate with a sealed TiO2 corrosion-resistant layer in a vacuum chamber of a vapor deposition device, maintaining the vacuum degree at 1 Pa; 2) turning on the MoS2 target, using an RF power supply as the power source, and setting the sputtering power of the RF power supply to 200-250W; 3) turning on the Ti target, using a DC power supply as the power source, setting the current of the DC power supply to 50-100A, the bias voltage to -200V~-400V, the duty cycle to 40%-60%, and the deposition time to 1-3h, so as to plate the composite coating on the surface of the substrate with the sealed TiO2 corrosion-resistant layer.
[0019] According to one aspect of the present disclosure, a composite coating obtained by the preparation method of the composite coating according to any one of the above-mentioned items is provided, wherein the composite coating includes a micro-arc oxidation TiO2 / MoS2 layer, a TiO2 sealing layer and a vapor-deposited Ti / MoS2 layer.
[0020] In an exemplary embodiment of the present disclosure, the thickness of the micro-arc oxidation TiO2 / MoS2 layer is 10-15 μm; the thickness of the TiO2 sealing layer is 1-1.5 μm; and the thickness of the vapor deposited Ti / MoS2 layer is 1-3 μm.
[0021] In an exemplary embodiment of the present disclosure, the atomic percentage of Ti in the vapor-deposited Ti / MoS2 layer is 2%-10%.
[0022] In the preparation method of the composite coating provided in the embodiment of the present disclosure, on the one hand, the activated MoS2 nanopowder is uniformly dispersed in the electrolyte to obtain a composite electrolyte; then the titanium alloy substrate is placed in the composite electrolyte for micro-arc oxidation treatment to generate a micro-arc oxidation layer with TiO2 / MoS2 on the surface of the titanium alloy substrate; then the titanium alloy substrate with the micro-arc oxidation layer of TiO2 / MoS2 is immersed in a sealing liquid, and then dried to obtain a substrate with a sealed TiO2 corrosion-resistant layer; finally, the substrate with the sealed TiO2 corrosion-resistant layer is placed In the vacuum chamber of the vapor deposition equipment, MoS2 target and Ti target are used as the anode, and the cathode is used. The coating treatment is carried out in an argon atmosphere with a vacuum degree of 1Pa to form a wear-resistant composite coating on the surface of the substrate with a sealed TiO2 corrosion-resistant layer; since micro-arc oxidation can be used to generate a micro-arc oxidation layer with TiO2 / MoS2 on the surface of the titanium alloy substrate, the friction reduction and wear resistance of the titanium alloy can be improved; on the other hand, since a multi-step sealing method can be used to obtain a sealed TiO2 corrosion-resistant layer, the corrosion resistance of the composite coating is further improved.
[0023] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings are incorporated into and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification, are used to explain the principles of the present disclosure. Obviously, the drawings described below are only some embodiments of the present disclosure, and those skilled in the art can derive other drawings based on these drawings without inventive effort.
[0025] Figure 1 A flow chart of a method for preparing a composite coating according to an exemplary embodiment of the present disclosure is schematically shown.
[0026] Figure 2 An example diagram of a composite coating obtained based on Example 2 according to an example embodiment of the present disclosure is schematically shown.
[0027] Figure 3 An example diagram of a micro-arc oxidation layer obtained based on Comparative Example 1 according to an example embodiment of the present disclosure is schematically shown.
[0028] Figure 4 A morphology diagram obtained after hot salt corrosion of a surface coating on a titanium alloy substrate according to an exemplary embodiment of the present disclosure is schematically shown.
[0029] Figure 5The figure schematically shows a morphology obtained after hot salt corrosion of a composite coating obtained based on Example 2 according to an exemplary embodiment of the present disclosure.
[0030] Figure 6 A morphology diagram obtained after hot salt etching of the surface of the micro-arc oxidation layer obtained in Comparative Example 1 according to an exemplary embodiment of the present disclosure is schematically shown. DETAILED DESCRIPTION
[0031] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the examples set forth herein; rather, these embodiments are provided so that the present disclosure will be more comprehensive and complete and will fully convey the concepts of the example embodiments to those skilled in the art. The described features, structures, or characteristics may be combined in any suitable manner in one or more embodiments. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or that other methods, components, devices, steps, etc. may be employed. In other cases, well-known technical solutions are not shown or described in detail to avoid obscuring various aspects of the present disclosure.
[0032] The terms "a", "an", "the" and "said" are used in this specification to indicate the presence of one or more elements / components, etc.; the terms "including" and "having" are used to express open-ended inclusion and mean that additional elements / components, etc. may exist in addition to the listed elements / components, etc.; the terms "first" and "second" are used only as labels and are not intended to limit the quantity of their objects.
[0033] In order to solve the problem that the related art cannot reduce the galvanic corrosion between titanium alloy and dissimilar materials and the hot salt corrosion in high temperature salt environment, the exemplary embodiment of the present disclosure first provides a method for preparing a composite coating. Figure 1 As shown, the preparation method of the composite coating may include the following steps:
[0034] Step S110, uniformly dispersing the activated MoS2 nanopowder in the electrolyte to obtain a composite electrolyte;
[0035] Step S120, placing the titanium alloy substrate in the composite electrolyte for micro-arc oxidation treatment to form a micro-arc oxidation layer with TiO2 / MoS2 on the surface of the titanium alloy substrate;
[0036] Step S130, immersing the titanium alloy substrate with the TiO2 / MoS2 micro-arc oxidation layer in a sealing liquid, followed by drying to obtain a substrate with a sealed TiO2 corrosion-resistant layer;
[0037] In step S140, the substrate with the sealed TiO2 corrosion-resistant layer is placed in the vacuum chamber of the vapor deposition equipment as the anode, and the MoS2 target and the Ti target are used as the cathode. The coating process is performed in an argon atmosphere with a vacuum degree of 1 Pa to form a wear-resistant composite coating on the surface of the substrate with the sealed TiO2 corrosion-resistant layer.
[0038] In the preparation method of the composite coating described above, on the one hand, the activated MoS2 nanopowder is uniformly dispersed in the electrolyte to obtain a composite electrolyte; then the titanium alloy substrate is placed in the composite electrolyte for micro-arc oxidation treatment to generate a micro-arc oxidation layer with TiO2 / MoS2 on the surface of the titanium alloy substrate; then the titanium alloy substrate with the micro-arc oxidation layer of TiO2 / MoS2 is immersed in a sealing liquid, and then dried to obtain a substrate with a sealed TiO2 corrosion-resistant layer; finally, the substrate with the sealed TiO2 corrosion-resistant layer is placed in a gas phase The vacuum chamber of the deposition equipment is used as the anode, and the MoS2 target and Ti target are used as the cathode. The coating treatment is carried out in an argon atmosphere with a vacuum degree of 1Pa to form a wear-resistant composite coating on the surface of the substrate with a sealed TiO2 corrosion-resistant layer; since the micro-arc oxidation method can be used to generate a micro-arc oxidation layer with TiO2 / MoS2 on the surface of the titanium alloy substrate, the friction reduction and wear resistance of the titanium alloy can be improved; on the other hand, since the multi-step sealing method can be used to obtain a sealed TiO2 corrosion-resistant layer, the corrosion resistance of the composite coating is further improved.
[0039] It should be further explained here that in the preparation method of the composite coating provided above, in the actual application process, first, a composite micro-arc oxidation layer is prepared in the first stage to improve the friction reduction and wear resistance of the composite coating; secondly, multi-step sealing is performed in the second stage to improve the corrosion resistance of the composite coating; in the third stage, a Ti / MoS2 composite coating is prepared by vapor deposition to further improve the friction reduction performance of the composite coating; finally, by optimizing the composition and structure of the composite coating on the surface of the titanium alloy, the problems of insufficient wear resistance, galvanic corrosion resistance and hot salt corrosion resistance of the titanium alloy are effectively overcome.
[0040] The following is a detailed explanation and description of each step involved in the preparation method of the composite coating. Specifically:
[0041] In step S110, the activated MoS2 nanopowder is uniformly dispersed in the electrolyte to obtain a composite electrolyte.
[0042] Specifically, the activated MoS2 nanopowder used in the composite electrolyte preparation process described herein is obtained by the following method: 10-20g of MoS2 nanopowder is immersed in a mixture of 0.05-0.1g of sodium lauryl sulfate and 200-300g of ethanol and stirred for 2h for activation treatment to obtain an activated mixed solution, and the activated mixed solution is dried and sieved to obtain activated MoS2 nanopowder. Further, under this premise, the preparation process of the composite electrolyte is obtained by the following method: 1-5g / L activated MoS2 nanopowder, 10-15g / L of sodium silicate, 0.5-1g / L of sodium hypophosphite, 2-5g / L of sodium tungstate, and 2-8ml / L of glycerol are mixed into an electrolyte, continuously stirred for 1-2h, and ultrasonically shaken for 0.5-1.5h to uniformly distribute the activated MoS2 nanopowder in the electrolyte.
[0043] In step S120, the titanium alloy substrate is placed in the composite electrolyte for micro-arc oxidation treatment to form a micro-arc oxidation layer with TiO2 / MoS2 on the surface of the titanium alloy substrate.
[0044] Specifically, in the preparation process of the micro-arc oxidation layer with TiO2 / MoS2, the frequency used in the micro-arc oxidation treatment process is 400-800 Hz, the positive duty cycle is 5-30%, the negative duty cycle is 5%-30%, the forward voltage is 350-500V, the negative voltage is 10-50V, and the oxidation time is 20-40min.
[0045] In step S130, the titanium alloy substrate with the TiO2 / MoS2 micro-arc oxidation layer is immersed in a sealing liquid and then dried to obtain a substrate with a sealed TiO2 corrosion-resistant layer.
[0046] Specifically, the sealing fluid is prepared by: 1) mixing 0.5-1.5 g / L of a silane coupling agent with 2-10 g / L of an organic solvent to obtain a solvent mixture; 2) stirring the solvent mixture for 36-48 hours to activate the solvent mixture, thereby obtaining an activated solvent; 3) adding 5-10 g / L of potassium fluorozirconate, 1-3 g / L of nano-titanium dioxide, and 1-5 g / L of triethanolamine to the activated solvent, followed by ultrasonic vibration for 0.5 hours to obtain the sealing fluid. The silane coupling agent described herein is KH507.
[0047] Under this premise, a substrate with a sealed TiO2 corrosion-resistant layer is prepared by the following method: a titanium alloy substrate with a TiO2 / MoS2 micro-arc oxidation layer is placed in a sealing liquid and soaked for 5-10 minutes, and the soaked titanium alloy substrate is placed in an oven and baked at 160°C for 15 minutes, and then the baking is repeated 3-5 times and then dried again for 30 minutes to obtain a substrate with a sealed TiO2 corrosion-resistant layer.
[0048] In step S140, the substrate with the sealed TiO2 corrosion-resistant layer is placed in the vacuum chamber of the vapor deposition equipment as the anode, and the MoS2 target and the Ti target are used as the cathode. The coating process is performed in an argon atmosphere with a vacuum degree of 1 Pa to form a wear-resistant composite coating on the surface of the substrate with the sealed TiO2 corrosion-resistant layer.
[0049] Specifically, the composite coating is prepared by: 1) placing a substrate with a sealed TiO2 corrosion-resistant layer in a vacuum chamber of a vapor deposition device and maintaining the vacuum degree at 1 Pa; 2) turning on the MoS2 target, using a radio frequency power supply, and setting the sputtering power of the radio frequency power supply to 200-250W; 3) turning on the Ti target, using a direct current power supply, setting the current of the direct current power supply to 50-100A, setting the bias voltage to -200V~-400V, the duty cycle to 40%-60%, and the deposition time to 1-3h, so as to plate the composite coating on the surface of the substrate with the sealed TiO2 corrosion-resistant layer.
[0050] Furthermore, the composite coating obtained based on the preparation method of the composite coating described above may include a micro-arc oxidation TiO2 / MoS2 layer, a TiO2 sealing layer and a vapor-deposited Ti / MoS2 layer; at the same time, the thickness of the micro-arc oxidation TiO2 / MoS2 layer is 10-15μm; the thickness of the TiO2 sealing layer is 1-1.5μm; the thickness of the vapor-deposited Ti / MoS2 layer is 1-3μm; further, the atomic percentage of Ti in the vapor-deposited Ti / MoS2 layer is 2%-10%; further, the composite coating obtained based on the exemplary embodiment of the present disclosure can be used for alloys such as TA2, TC4, TC6, TC11, and Ti5331.
[0051] At this point, the preparation method of the composite coating recorded in the exemplary embodiment of the present disclosure has been fully realized. Based on the above-mentioned contents, it can be known that the preparation method of the composite coating recorded in the exemplary embodiment of the present disclosure has at least the following advantages: on the one hand, the TC6 alloy is treated by micro-arc oxidation, and the activated MoS2 nanopowder is evenly dispersed into the electrolyte to obtain a TiO2 / MoS2 coating, which can greatly improve the friction reduction and wear resistance of the TC6 alloy; on the other hand, a multi-step sealing method is adopted to obtain a TiO2 corrosion-resistant layer, which further improves the corrosion resistance of the coating; finally, a physical vapor deposition method is used to prepare a MoS2 / Ti friction reduction layer; on the other hand, the exemplary embodiment of the present disclosure prepares a composite coating on the surface of the TC6 alloy by combining micro-arc oxidation with physical vapor deposition. It adopts a typical multi-layer design, combines the advantages of different coating components, greatly improves its friction reduction and wear resistance and hot salt corrosion resistance, can meet the use requirements of a variety of complex working conditions, and has good applicability.
[0052] The following will further explain and illustrate the preparation method of the composite coating in conjunction with specific examples. Specifically:
[0053] Example 1: A method for preparing a composite coating and a composite coating, comprising the following steps:
[0054] Step 1: Evenly disperse the activated MoS2 nanopowder in the electrolyte to obtain a composite electrolyte.
[0055] Step 2: placing the clean titanium alloy substrate in the composite electrolyte of step 1 for micro-arc oxidation treatment to obtain a TiO2 / MoS2 micro-arc oxidation layer on the surface of the titanium alloy substrate.
[0056] Step 3: Immerse the titanium alloy substrate with the TiO2 / MoS2 micro-arc oxidation layer in step 2 in a sealing liquid, and then dry it to obtain a substrate with a sealed TiO2 corrosion-resistant layer.
[0057] Step 4: Place the sample obtained in step 3 in the vacuum chamber of the vapor deposition equipment as the anode, use MoS2 target and Ti target as the cathode, and perform coating treatment in an argon atmosphere with a vacuum degree of 1 Pa to form a MoS2 / Ti layer on the surface to obtain a wear-resistant composite coating.
[0058] In step 1 of this embodiment, the activation method of MoS2 nanopowder is: immersing 10g of MoS2 nanopowder in a mixture of 0.05g of sodium lauryl sulfate and 200g of ethanol and stirring for 2h for activation treatment, and then drying and sieving to obtain the activated MoS2 nanopowder.
[0059] Wherein, in the step one of this embodiment, the composite electrolyte preparation method is to be MoS after 1g / L activationNano powder, 10g / L sodium silicate, 0.5g / L sodium hypophosphite, 2g / L sodium tungstate, 4ml / L glycerol are mixed with electrolyte, continuously stirred for 1h, ultrasonic oscillation 0.5h, by the activated MoSNano powder is evenly distributed in the electrolyte. Meanwhile, in the step two of this embodiment, TiO2 / MoS2 micro-arc oxidation layer preparation method is frequency 400Hz, positive duty cycle 30%, negative duty cycle 30%, forward voltage 350V, negative voltage 10V, oxidation time 40min. Further, in the step three of this embodiment, the sealing liquid preparation method is to mix 1.5g / L KH507 with 10g / L organic solvent, stir for 48h to activate, then add 10g / L potassium fluorozirconate, 3g / L nano titanium dioxide, 3g / L triethanolamine ultrasonic oscillation 0.5h. Furthermore, in step three of this embodiment, the sealing layer preparation method is to place the substrate with the TiO2 / MoS2 micro-arc oxidation layer in step two in the sealing liquid and soak it for 5 minutes, then place it in an oven and bake it at 160°C for 15 minutes, repeat 3 times and then dry it for 30 minutes to obtain a substrate with a sealed TiO2 corrosion-resistant layer. Finally, in step four of this embodiment, the Ti / MoS2 layer preparation method is to place the substrate obtained in step three in a vacuum chamber of a vapor deposition device, maintain the vacuum degree at 1Pa, and then turn on the MoS2 target, the power supply used is a radio frequency power supply, and the sputtering power is set to 200W. Turn on the Ti target, the power supply used is a DC power supply, and the current is set to 50A. The bias voltage is set to -200V, the duty cycle is 40%, the deposition time is 1h, and the Ti / MoS2 composite layer is plated.
[0060] Furthermore, the composite coating in this embodiment consists of a micro-arc oxidation TiO2 / MoS2 layer, a TiO2 sealing layer, and a vapor-deposited Ti / MoS2 layer. The TiO2 / MoS2 layer is 10 μm thick, the TiO2 sealing layer is 1 μm thick, and the vapor-deposited Ti / MoS2 layer is 1 μm thick. The atomic percentage of Ti in the Ti / MoS2 layer is 2%.
[0061] Example 2: A method for preparing a composite coating and the composite coating, comprising the following steps:
[0062] Step 1: Evenly disperse the activated MoS2 nanopowder in the electrolyte to obtain a composite electrolyte.
[0063] Step 2: placing the clean titanium alloy substrate in the composite electrolyte of step 1 for micro-arc oxidation treatment to obtain a TiO2 / MoS2 micro-arc oxidation layer on the surface of the titanium alloy substrate.
[0064] Step 3: Immerse the titanium alloy substrate with the TiO2 / MoS2 micro-arc oxidation layer in step 2 in a sealing liquid, and then dry it to obtain a substrate with a sealed TiO2 corrosion-resistant layer.
[0065] Step 4: Place the sample obtained in step 3 in the vacuum chamber of the vapor deposition equipment as the anode, use MoS2 target and Ti target as the cathode, and perform coating treatment in an argon atmosphere with a vacuum degree of 1 Pa to form a MoS2 / Ti layer on the surface to obtain a wear-resistant composite coating.
[0066] Wherein, in the step one of the embodiment, MoS2 the activation method of nano powder is: by 20gMoS2 nano powder is immersed in the mixed solution of 0.08g sodium lauryl sulfate and 250g ethanol and stirs 2h and carries out activation treatment, and sieves through drying afterwards, can obtain the MoS after activation2 nano powder.Meanwhile, in the step one of the embodiment, composite electrolyte preparation method is the MoS after 3g / L activation2 nano powder, 12g / L sodium silicate, 0.8g / L sodium hypophosphite, 4g / L sodium tungstate, 2ml / L glycerol are mixed with electrolyte, continuously stir 1.5h, ultrasonic oscillation 1h, by the MoS after activation2 nano powder is evenly distributed in electrolyte.Secondly, in the step 2 of the embodiment, TiO2 / MoS2 micro-arc oxidation layer preparation method is frequency 600Hz, positive duty cycle 15%, negative duty cycle 15%, forward voltage 450V, negative voltage 30V, oxidation time 30min. Furthermore, in step three of this embodiment, the sealing liquid preparation method is to mix 1g / L KH507 with 5g / L organic solvent, stir for 48h for activation, and then add 8g / L potassium fluorozirconate, 1.5g / L nano titanium dioxide, and 5g / L triethanolamine for ultrasonic vibration for 0.5h. Furthermore, in step three of this embodiment, the sealing layer preparation method is to place the substrate with the TiO2 / MoS2 micro-arc oxidation layer in step two in the sealing liquid and soak it for 5min, then place it in an oven at 160℃ for 15min, repeat 4 times and then dry it for 30min to obtain a substrate with a sealed TiO2 corrosion-resistant layer. Finally, in step four of this embodiment, the Ti / MoS2 layer preparation method is to place the substrate obtained in step three in a vacuum chamber of a vapor deposition equipment, maintain the vacuum at 1Pa, and then turn on the MoS2 target, the power supply used is a radio frequency power supply, and the sputtering power is set to 220W. Turn on the Ti target, the power supply used is a DC power supply, and the current size is set to 100A. The bias voltage was set to -300 V, the duty cycle was 50%, the deposition time was 2 h, and the Ti / MoS2 composite layer was plated.
[0067] Furthermore, the composite coating in this embodiment is composed of a micro-arc oxidation TiO2 / MoS2 layer, a TiO2 sealing layer, and a vapor-deposited Ti / MoS2 layer. The thickness of the TiO2 / MoS2 layer in the composite coating is 12 μm, the TiO2 sealing layer is 1.2 μm, the vapor-deposited Ti / MoS2 layer is 1.8 μm, and the atomic percentage of Ti in the Ti / MoS2 layer is 10%. The electron microscope scanning image of the composite coating obtained in this embodiment can be referenced. Figure 2 shown.
[0068] Example 3: A method for preparing a composite coating and the composite coating, comprising the following steps:
[0069] Step 1: Evenly disperse the activated MoS2 nanopowder in the electrolyte to obtain a composite electrolyte.
[0070] Step 2: placing the clean titanium alloy substrate in the composite electrolyte of step 1 for micro-arc oxidation treatment to obtain a TiO2 / MoS2 micro-arc oxidation layer on the surface of the titanium alloy substrate.
[0071] Step 3: Immerse the titanium alloy substrate with the TiO2 / MoS2 micro-arc oxidation layer in step 2 in a sealing liquid, and then dry it to obtain a substrate with a sealed TiO2 corrosion-resistant layer.
[0072] Step 4: Place the sample obtained in step 3 in the vacuum chamber of the vapor deposition equipment as the anode, use MoS2 target and Ti target as the cathode, and perform coating treatment in an argon atmosphere with a vacuum degree of 1 Pa to form a MoS2 / Ti layer on the surface to obtain a wear-resistant composite coating.
[0073] Wherein, in the step one of this embodiment, MoS2 the activation method of nano powder is: by 20gMoS2 nano powder is immersed in the mixed solution of 0.1g sodium lauryl sulfate and 300g ethanol and stirs 2h and carries out activation treatment, and sieves through drying afterwards, can obtain the MoS after activation2 nano powder.Meanwhile, in the step one of this embodiment, composite electrolyte preparation method is the MoS after 5g / L activation2 nano powder, 15g / L sodium metasilicate, 1g / L sodium hypophosphite, 5g / L sodium tungstate, 4ml / L glycerol are mixed with electrolyte, continuously stir 1.5h, ultrasonic oscillation 1.5h, by the MoS after activation2 nano powder is evenly distributed in electrolyte.Secondly, in the example step 2 of this implementation, TiO2 / MoS2 micro-arc oxidation layer preparation method is frequency 600Hz, positive duty cycle 15%, negative duty cycle 15%, forward voltage 450V, negative voltage 30V, oxidation time 30min. Furthermore, in step 3 of this embodiment, the sealing liquid is prepared by mixing 1g / L KH507 with 5g / L organic solvent, stirring for 48h for activation, and then adding 8g / L potassium fluorozirconate, 1.5g / L nano-titanium dioxide, and 5g / L triethanolamine for ultrasonic vibration for 0.5h. Furthermore, in step 3 of this embodiment, the sealing layer is prepared by placing the substrate with the TiO2 / MoS2 micro-arc oxidation layer in step 2 in the sealing liquid and soaking it for 5min, then placing it in an oven at 160°C for 15min, repeating 4 times and then drying it for 30min to obtain a substrate with a sealed TiO2 corrosion-resistant layer. Finally, in step 4 of this embodiment, the Ti / MoS2 layer is prepared by placing the substrate obtained in step 3 in a vacuum chamber of a vapor deposition equipment, maintaining the vacuum at 1Pa, and then turning on the MoS2 target, using a radio frequency power supply, and setting the sputtering power to 250W. Turning on the Ti target, using a DC power supply, and setting the current to 100A. The bias voltage was set to -400 V, the duty cycle was 60%, the deposition time was 3 h, and the Ti / MoS2 composite layer was plated.
[0074] Furthermore, the composite coating in this embodiment consists of a micro-arc oxidation TiO2 / MoS2 layer, a TiO2 sealing layer, and a vapor-deposited Ti / MoS2 layer. The TiO2 / MoS2 layer is 13 μm thick, the TiO2 sealing layer is 1.2 μm thick, and the vapor-deposited Ti / MoS2 layer is 2 μm thick. The atomic percentage of Ti in the Ti / MoS2 layer is 8%.
[0075] Example 4: A method for preparing a composite coating and the composite coating, comprising the following steps:
[0076] Step 1: Evenly disperse the activated MoS2 nanopowder in the electrolyte to obtain a composite electrolyte.
[0077] Step 2: placing the clean titanium alloy substrate in the composite electrolyte of step 1 for micro-arc oxidation treatment to obtain a TiO2 / MoS2 micro-arc oxidation layer on the surface of the titanium alloy substrate.
[0078] Step 3: Immerse the titanium alloy substrate with the TiO2 / MoS2 micro-arc oxidation layer in step 2 in a sealing liquid, and then dry it to obtain a substrate with a sealed TiO2 corrosion-resistant layer.
[0079] Step 4: Place the sample obtained in step 3 in the vacuum chamber of the vapor deposition equipment as the anode, use MoS2 target and Ti target as the cathode, and perform coating treatment in an argon atmosphere with a vacuum degree of 1 Pa to form a MoS2 / Ti layer on the surface to obtain a wear-resistant composite coating.
[0080] In step 1 of this embodiment, the activation method of MoS2 nanopowder is as follows: 10g of MoS2 nanopowder is immersed in a mixture of 0.1g / L sodium dodecyl sulfate and 200g of ethanol and stirred for 2h for activation treatment, and then dried and sieved to obtain the activated MoS2 nanopowder.
[0081] Wherein, in the step one of this embodiment, the composite electrolyte preparation method is to be MoS after 5g / L activationNano powder, 15g / L sodium silicate, 1g / L sodium hypophosphite, 5g / L sodium tungstate, 8ml / L glycerol are mixed with electrolyte, continuously stirred for 2h, ultrasonic oscillation 1.5h, by the activated MoSNano powder is evenly distributed in the electrolyte. Meanwhile, in the step two of this embodiment, TiO2 / MoS2 micro-arc oxidation layer preparation method is frequency 800Hz, positive duty cycle 5%, negative duty cycle 5%, forward voltage 500V, negative voltage 50V, oxidation time 20min. Secondly, in the step three of this embodiment, the sealing liquid preparation method is to mix 0.5g / L KH507 with 2g / L organic solvent, stir for 36h to activate, then add 5g / L potassium fluorozirconate, 1g / L nano titanium dioxide, 1g / L triethanolamine ultrasonic oscillation 0.5h. Furthermore, in step three of this embodiment, the sealing layer preparation method is to place the substrate with the TiO2 / MoS2 micro-arc oxidation layer in step two in the sealing liquid and soak it for 5 minutes, then place it in an oven and bake it at 160°C for 15 minutes, repeat 5 times and then dry it for 30 minutes to obtain a substrate with a sealed TiO2 corrosion-resistant layer. Finally, in step four of this embodiment, the Ti / MoS2 layer is prepared by placing the substrate obtained in step three in a vacuum chamber of a vapor deposition device, maintaining the vacuum degree at 1 Pa, and then turning on the MoS2 target, using a radio frequency power supply, and setting the sputtering power to 250W. Turn on the Ti target, use a DC power supply, and set the current to 100A. The bias voltage is set to -400V, the duty cycle is 60%, the deposition time is 3 hours, and a Ti / MoS2 composite layer is plated.
[0082] Furthermore, the composite coating in this embodiment consists of a micro-arc oxidation TiO2 / MoS2 layer, a TiO2 sealing layer, and a vapor-deposited Ti / MoS2 layer. The TiO2 / MoS2 layer is 15 μm thick, the TiO2 sealing layer is 1 μm thick, and the vapor-deposited Ti / MoS2 layer is 2 μm thick. The atomic percentage of Ti in the Ti / MoS2 layer is 8%.
[0083] Comparative Example 1:
[0084] A method for preparing a wear-resistant composite coating on a titanium alloy surface may include the following steps:
[0085] Step 1: Evenly disperse the activated MoS2 nanopowder in the electrolyte to obtain a composite electrolyte.
[0086] Step 2: placing the clean titanium alloy substrate in the composite electrolyte of step 1 for micro-arc oxidation treatment to obtain a TiO2 / MoS2 micro-arc oxidation layer on the surface of the titanium alloy substrate.
[0087] Wherein, in the step one of this embodiment, MoS2 the activation method of nano powder is: by 20gMoS2 nano powder is immersed in the mixed solution of 0.08g sodium lauryl sulfate and 250g ethanol and stirs 2h and carries out activation treatment, and sieves through drying afterwards, can obtain the MoS after activation2 nano powder.Simultaneously, in the step one of this embodiment, composite electrolyte preparation method is the MoS after 3g / L activation2 nano powder, 12g / L sodium silicate, 0.8g / L sodium hypophosphite, 4g / L sodium tungstate, 2ml / L glycerol are mixed with electrolyte, continuously stirred 1.5h, ultrasonic oscillation 1h, by the MoS after activation2 nano powder is evenly distributed in electrolyte.
[0088] Moreover, the coating obtained in this comparative example is a micro-arc oxidation TiO2 / MoS2 layer. At the same time, the electron microscope scanning diagram of the micro-arc oxidation layer obtained based on this comparative example can be referred to Figure 3 shown.
[0089] Figure 4 The morphology obtained after hot salt corrosion on a titanium alloy substrate is schematically shown; Figure 5 The morphology obtained after hot salt corrosion on the surface of the composite coating obtained in Example 2 is schematically shown; Figure 6 The morphology of the micro-arc oxidation layer obtained in Comparative Example 1 after hot salt corrosion is schematically shown. Figure 4-Figure 6 It can be seen that, on the one hand, for the composite coating obtained by applying the above-mentioned Example 2 of the present disclosure, compared with the titanium alloy substrate and the micro-arc oxidation layer, the coating preparation scheme of Example 2 can significantly improve the corrosion resistance of the titanium alloy. Furthermore, Table 1 shows the friction coefficient and wear rate of the titanium alloy surface coating of the titanium alloy substrate, Example 2 of the present invention and the comparative example. It can be seen that compared with the titanium alloy substrate, the composite coating obtained in Example 2 of the present disclosure has significantly improved friction reduction and wear resistance. Compared with the comparative example, the wear resistance of the composite coating obtained in Example 2 of the present disclosure is similar, and the friction reduction is significantly improved.
[0090] Table 1
[0091]
[0092] Furthermore, the figures above are merely illustrative of the processes included in the methods according to exemplary embodiments of the present disclosure and are not intended to be limiting. It is readily understood that the processes illustrated in the figures above do not indicate or limit the temporal order of these processes. Furthermore, it is readily understood that these processes may be executed synchronously or asynchronously, for example, in multiple modules.
[0093] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any variations, uses, or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary techniques in the art not disclosed herein. The description and examples are to be considered as exemplary only, with the true scope and spirit of the present disclosure being indicated by the appended claims.
[0094] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes can be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.
Claims
1. A method for preparing a composite coating, characterized in that: include: Step 1: Evenly dispersing the activated MoS2 nanopowder in the electrolyte to obtain a composite electrolyte; Step 2: placing the titanium alloy substrate in the composite electrolyte for micro-arc oxidation treatment to generate a micro-arc oxidation layer with TiO2 / MoS2 on the surface of the titanium alloy substrate; Step 3: immersing the titanium alloy substrate with the TiO2 / MoS2 micro-arc oxidation layer into a sealing liquid, followed by drying to obtain a substrate with a sealed TiO2 corrosion-resistant layer; Step 4: placing the substrate with the sealed TiO2 corrosion-resistant layer in a vacuum chamber of a vapor deposition device as an anode, using a MoS2 target and a Ti target as a cathode, and performing a coating process in an argon atmosphere with a vacuum degree of 1 Pa to form a wear-resistant composite coating on the surface of the substrate with the sealed TiO2 corrosion-resistant layer; The sealing liquid is prepared in the following manner: 1) 0.5-1.5 g / L of a silane coupling agent is mixed with 2-10 g / L of an organic solvent to obtain a solvent mixture; 2) the solvent mixture is stirred for 36-48 hours to activate the solvent mixture to obtain a solvent activation result; 3) 5-10 g / L of potassium fluorozirconate, 1-3 g / L of nano titanium dioxide and 1-5 g / L of triethanolamine are added to the solvent activation result and ultrasonically vibrated for 0.5 hours to obtain the sealing liquid.
2. The method for preparing the composite coating according to claim 1, characterized in that: The activated MoS2 nanopowder used in the preparation process of the composite electrolyte is obtained in the following way: 10-20g of MoS2 nanopowder is immersed in a mixture of 0.05-0.1g of sodium dodecyl sulfate and 200-300g of ethanol and stirred for 2h for activation treatment to obtain an activated mixed solution, and the activated mixed solution is dried and sieved to obtain activated MoS2 nanopowder.
3. The method for preparing the composite coating according to claim 1, characterized in that: The preparation process of the composite electrolyte is obtained by the following method: 1-5g / L activated MoS2 nanopowder, 10-15g / L sodium silicate, 0.5-1g / L sodium hypophosphite, 2-5g / L sodium tungstate, and 2-8ml / L glycerol are prepared into an electrolyte, which is continuously stirred for 1-2h and ultrasonically vibrated for 0.5-1.5h to evenly distribute the activated MoS2 nanopowder in the electrolyte.
4. The method for preparing the composite coating according to claim 1, characterized in that: In the preparation process of the micro-arc oxidation layer with TiO2 / MoS2, the frequency used in the micro-arc oxidation process is 400-800Hz, the forward duty cycle is 5-30%, the negative duty cycle is 5%-30%, the forward voltage is 350-500V, the negative voltage is 10-50V, and the oxidation time is 20-40min.
5. The method for preparing the composite coating according to claim 1, characterized in that: The substrate with a sealed TiO2 corrosion-resistant layer is prepared in the following manner: a titanium alloy substrate with a TiO2 / MoS2 micro-arc oxidation layer is placed in a sealing liquid and immersed for 5-10 minutes, and the immersed titanium alloy substrate is placed in an oven and baked at 160°C for 15 minutes, and then the baking is repeated 3-5 times and then dried again for 30 minutes to obtain a substrate with a sealed TiO2 corrosion-resistant layer.
6. The method for preparing the composite coating according to claim 1, characterized in that: The composite coating is prepared by the following method: 1) placing a substrate with a sealed TiO2 corrosion-resistant layer in a vacuum chamber of a vapor deposition device and maintaining the vacuum degree at 1 Pa; 2) turning on the MoS2 target, using a radio frequency power supply as the power source, and setting the sputtering power of the radio frequency power supply to 200-250W; 3) turning on the Ti target, using a direct current power supply as the power source, setting the current of the direct current power supply to 50-100A, setting the bias voltage to -200V~-400V, the duty cycle to 40%-60%, and the deposition time to 1-3h, so as to plate the composite coating on the surface of the substrate with the sealed TiO2 corrosion-resistant layer.
7. A composite coating obtained by the method for preparing a composite coating according to any one of claims 1 to 6, characterized in that: The composite coating comprises a micro-arc oxidation TiO2 / MoS2 layer, a TiO2 pore sealing layer and a vapor-deposited Ti / MoS2 layer.
8. The composite coating according to claim 7, characterized in that: The thickness of the micro-arc oxidation TiO2 / MoS2 layer is 10-15 μm; the thickness of the TiO2 sealing layer is 1-1.5 μm; and the thickness of the vapor deposited Ti / MoS2 layer is 1-3 μm.
9. The composite coating according to claim 7, characterized in that: The atomic percentage of Ti in the vapor deposited Ti / MoS2 layer is 2%-10%.
Citation Information
Patent Citations
Preparation method of molybdenum disulfide base lubricating wear-resistant composite film
CN101906614A
Molybdenum disulfide-aluminum self-lubricating coating suitable for titanium alloy and application of molybdenum disulfide-aluminum self-lubricating coating
CN115491643A
Method for in-situ synthesis of graphene Y2O3 / ZrO2 / MgO composite ceramic membrane on surface of magnesium alloy building template
CN119040989A